A population-based Swedish Twin and Sibling Study of cannabis, stimulant and sedative abuse in men. (1st April 2015) - Kendler, Kenneth S.; Ohlsson, Henrik; Maes, Hermine H.; Sundquist, Kristina; Lichtenstein, Paul; Sundquist, Jan
Highlights: We studied drug abuse using high quality Swedish public registries. Our results from population registers were similar to those from interview studies. Genetic risk for abuse of particular classes of drugs is largely non-specific. Some specific genetic effects were seen, most strongly for cannabis abuse. Abstract: Background: Prior studies, utilizing interview-based assessments, suggest that most of the genetic risk factors for drug abuse (DA) are non-specific with a minority acting specifically on risk for abuse of particular psychoactive substance classes. We seek to replicate these findings using objective national registry data. Methods: We examined abuse of cannabis, stimulants (including cocaine) and sedatives ascertained from national Swedish registers in male–male monozygotic (1720 pairs) and dizygotic twins (1219 pairs) combined with near-age full siblings (76, 457 pairs) to provide sufficient power. Modeling was performed using Mx. Results: A common pathway model fitted better than an independent pathway model. The latent liability to DA was highly heritable but also influenced by shared environment. Cannabis, stimulant and sedative abuse all loaded strongly on the common factor. Estimates for the total heritability for the three forms of substance abuse ranged from 64 to 70%. Between 75 and 90% of that genetic risk was non-specific, coming from the common factor with the remainder deriving from substance specific genetic risk factors. By contrast, all of the shared environmental effects, which accounted for 18–20% of the variance in liability, were non-specific. Conclusions: In accord with prior studies based on personal interviews, the large preponderance of genetic risk factors for abuse of specific classes of psychoactive substance are non-specific. These results suggest that genetic variation in the primary sites of action of the psychoactive drugs, which differ widely across most drug classes, play a minor role in human individual differences in risk for DA.